The MuSeS project: a mixed methods study to increase understanding of the role of settlement and multicultural services in supporting migrant and refugee women experiencing violence in Australia - Cathy Vaughan; Yara Jarallah; Adele Murdolo; Linda Murray; Regina Quiazon; Karen Block; Lana Zannettino (BMC, 2019)
Abstract Background Violence against women is a major human rights and public health issue globally. The experience of violence affects women across Australia, including the large number of migrant and refugee women who permanently or temporarily resettle in the country. Many women who experience violence find it difficult to access support, and evidence suggests women who have resettled in Australia face additional barriers to violence-specific services. Previous research, however, indicates many migrant and refugee women experiencing violence have contact with, and may disclose violence to, settlement and multicultural services. There has been limited research documenting current knowledge of, and practices by, settlement and multicultural services in relation to violence. The MuSeS project will address this knowledge gap and identify strategies settlement and multicultural services can use to better support women experiencing violence. Methods This mixed methods research project will be conducted in six geographic communities across three Australian states: South Australia, Tasmania and Victoria. The different migration and resettlement patterns seen in these jurisdictions will enable generation of data relevant to settings across the country. The project has been designed in consultation with partner organisations from the settlement and multicultural service sector to ensure the research addresses their concerns and priorities. A mix of quantitative and qualitative methods will be used to generate rich data to inform strategies for settlement and multicultural services to better support women experiencing violence. These methods include an anonymous online survey of settlement and multicultural service providers to assess current knowledge, practices and professional development needs; in-depth interviews with settlement, multicultural and specialist (refugee) mental health service providers; in-depth interviews with refugee women; and focus group discussions with frontline workers and volunteers working with settlement and multicultural services. Discussion Findings from this two-year research project will generate an in-depth understanding of the current and potential role of Australian settlement and multicultural services in supporting migrant and refugee women experiencing violence, and inform strategies to strengthen services' capacity to appropriately respond. Given the prevalence of violence against women globally, findings will be useful for services engaging with migrant and refugee populations around the world.